Life cycles and ethics of ageing - Solange Aparecida de Souza Monteiro (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
This bibliographic study seeks to understand the experience of aging. From the choices lived by the subjects who are aging, health becomes essential for their autonomy, the right to find meaning to live until the so-called Third Age. The aim of this article is to discuss and reflect the main concerns of people with aging, who consider that with aging lose their identity, they still feel that they do not identify with their chronological age and with the fact that they do not feel Aged. Based on Foucault's contributions, in his genealogical researches, we intend to think of aging as an ethical choice linked to an aesthetic of existence and health as a dimension of life that does not exclude sexuality from death and disease.